Effect of Early and Conventional Sowings on Soybean Establishment Quality, Nodulation, and Early Biomass Development Under Inoculation with Rhizoctonia solani - Jay Ram Lamichhane; Jean-Noël Aubertot (PhytoFrontiers, 2021)
Early sowing has potential to reduce negative impacts of summer drought on soybean productivity in southern Europe. However, performing early sowing into cool and moist soil conditions may increase risks of soilborne pathogens that cause damping-off disease. We investigated whether and to what extent soybean germination, emergence, nodulation, and early biomass growth was affected when inoculated with Rhizoctonia solani, an important causal agent of damping-off disease. We conducted this study through four complementary approaches: (i) in vitro laboratory tests, (ii) field experiments including two sowing dates (early and conventional), (iii) growth-chamber experiments, and (iv) modeling. The pathogen caused disease symptoms and significantly reduced (P ≤ 0.001) radicle growth in vitro but failed to cause disease under field or growth-chamber conditions. No biological suppressiveness of the field soil to R. solani was found when tested in the growth chamber. Final field emergence rates ranged from 72 to 92% for early and conventional sowing, respectively, while those in the growth chamber ranged from 80 to 100%. Under field conditions, abiotic stresses were the major causes of nonemergence while biotic stresses had only minor impact on seedling emergence. A significant effect of sowing date (P < 0.001) was observed on the average shoot and root length and on the number of average nodules per plantlet. The overall prediction quality of the SIMPLE model was very good for both sowing dates. The contrasts between laboratory and field experiments in terms of disease development, time to emergence, and early growth parameters are discussed.[Figure: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.